(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2024)
This article is devoted to periphrasis, which are important tool in language that enriches communication, adds depth to expression, and improves understanding. A periphrasis is one of the tools for communication and the use of linguistic periphrasis boosts expressiveness to our conversation and written texts. In this article, I will delve into the significance of linguistic periphrases and highlight their role in enhancing communication.